EKOLOGI MASYARAKAT MINANGKABAU PADA LAGU SOSOH DALAM UPACARA TABUIK DI PARIAMAN, SUMATRA BARAT - Cameron Malik (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2023)
The Sosoh song is played during the Tabuik ceremony. Its purpose is to facilitate the battle in the ritual which aims to represent the war experienced by Husein in Karbala, Iraq. The aim of this research is to explore the relationship between the performance of the Sosoh song and the ecological system in Minangkabau culture. This study uses ethnographic methods with primary sources of data being field notes, interviews, and documentation. The results of this study show that the Sosoh song is not only related to the ritual context but also to Minangkabau culture as a whole. This is demonstrated by the reciprocal relationship between the song and cultural construction. It can be seen that the Sosoh song is an actualization of how the concept of resilience in maintaining sovereignty in a nagari within the cultural context is embodied in warfare during the ceremony. In conclusion, the Sosoh song has a significant role in Minangkabau culture and is not just limited to the context of the Tabuik ceremony. The research findings can help to raise awareness and appreciation of the cultural heritage of Minangkabau, and could potentially be used to promote the preservation and development of this unique culture.